EFEKTIVITAS DANA POS BANTUAN HUKUM ADVOKAT INDONESIA TERHADAP HAK TERSANGKA - S, Jumadi. (Magister Ilmu Hukum Universitas Indonesia Timur, 2014)
The Effectivity of Law Aid Fund Post of Indonesian Advokad to the Rights of Suspect In Sidrap Regency (supervised by Rachmad Baro dan Lukman). This study aims to determine extent to which of effectiveness of Law Aid Post of Indonesian Advokad to the right of suspect to get a law assistance, and to find out how the constraints in giving of law assistance to a suspect without a fee in Sidrap regency.A research method or technique of data collection in this study by documents and data necessary in researched intensely in order to support and increase the credibility and evidence of an occurrence, then researchers conducted interview to informant in relation to the studied problem .The result obtained are effectiveness of Law Aid Post of Indonesian Advokad to the right of suspect in Sidrap not run effectively since from 2011-2013. and the constraints of the right suspect that do not use Law Aid Institution because they could not afford to pay fee for law adviser which will be used. They the problem of study, then are afraid if law adviser requests surcharge are not know the function and role of a law adviser for them they as well as lack of suspect knowledge about law.